Draft Genome Sequence of Pectobacterium wasabiae Strain CFIA1002 - Yuan, Kat (Xiaoli) (American Society for Microbiology, 2014)
Pectobacterium wasabiae, originally causing soft rot disease in horseradish in Japan, was recently found to cause blackleg-like symptoms on potato in the United States, Canada, and Europe. A draft genome sequence of a Canadian potato isolate of P. wasabiae CFIA1002 will enhance the characterization of its pathogenicity and host specificity features.